2022
DOI: 10.1097/corr.0000000000002253
|View full text |Cite
|
Sign up to set email alerts
|

No Strength Differences Despite Greater Posterior Rotator Cuff Intramuscular Fat in Patients With Eccentric Glenohumeral Osteoarthritis

Abstract: BackgroundWhen nonoperative measures do not alleviate the symptoms of glenohumeral osteoarthritis (OA), patients with advanced OA primarily are treated with anatomic total shoulder arthroplasty (TSA). It is unknown why TSAs performed in patients with eccentric (asymmetric glenoid wear) compared with concentric (symmetric glenoid wear) deformities exhibit higher failure rates, despite surgical advances. Persistent disruption of the posterior-to-anterior rotator cuff (RC) force couple resulting from posterior RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…The findings of the current study support this theory, as patients who had undergone TSA had relatively weaker internal rotation compared with control participants. While relative internal rotation weakness has been shown to exist in patients before TSA compared with control participants (range of mean difference, 2.9% to 7.6% of SM) 19 , the degree of weakness was greater after TSA (range, 10.9% to 13.6% of SM). Relative subscapularis weakness after TSA may offset underlying external rotator weakness.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The findings of the current study support this theory, as patients who had undergone TSA had relatively weaker internal rotation compared with control participants. While relative internal rotation weakness has been shown to exist in patients before TSA compared with control participants (range of mean difference, 2.9% to 7.6% of SM) 19 , the degree of weakness was greater after TSA (range, 10.9% to 13.6% of SM). Relative subscapularis weakness after TSA may offset underlying external rotator weakness.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, 1D dynamometers cannot discern the contribution of rotation to functional combined motions (e.g., adduction with rotation). Prior work has demonstrated posterior RC muscle deficiency in patients with eccentric deformity before TSA 7 , 19 , which is theorized to persist and contribute to TSA failures in this subgroup. However, postoperative strength has not been compared according to preoperative deformity types, to our knowledge, so it remains unknown whether patients with eccentric deformity exhibit relative external rotation weakness after TSA.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies evaluating imbalance in horizontal torque relied mainly on imaging [2,6]. The current study [4] relies on a clinical evaluation of torque production in a single posture while a patient performs isometric motions in different directions, where the goal is to determine whether there is a correlation with the onset of pain. Considerable uncertainty persists regarding the origin of pain in patients with osteoarthritis; it is unclear how joint deformity, cuff inflammation, synovitis, and subchondral bone contribute to it.…”
Section: Corr Insights®: No Strength Differences Despite Greater Post...mentioning
confidence: 99%
“…In this issue of Clinical Orthopaedics and Related Research ® , Coats-Thomas et al [4] attempted to clarify the question of whether there are differences in muscle strength regarding internal and external rotation of the rotator cuff and any relation to wear status, concentric or eccentric, of the glenoid in patients with shoulder osteoarthritis. The authors concluded that eccentric shoulders do not demonstrate external rotation weakness compared with concentric shoulders; The opinions expressed are those of the writer, and do not reflect the opinion or policy of CORR ® or The Association of Bone and Joint Surgeons ® .…”
Section: Corr Insights®: No Strength Differences Despite Greater Post...mentioning
confidence: 99%